Clinical outcomes after ticagrelor and clopidogrel in Chinese post-stented patients. (November 2019) - Sun, Yang; Li, Chenze; Zhang, Lina; Yu, Ting; Ye, Heng; Yu, Bo; Tao, Min; Jiang, Jiangang; Yan, Jiangtao; Wang, Yan; Zeng, Hesong; Shen, Xiaoqing; et al.
Abstract: Background and aims: International guidelines recommend ticagrelor over clopidogrel as preferred antiplatelet agent in patients following coronary stenting. However, no large real-life evidence is available in East Asians in general, and Chinese in particular, with regard to associated clinical outcomes. The present study aimed to assess the early and delayed outcomes after ticagrelor versus clopidogrel in post stenting Chinese patients. Methods: We conducted the pre-specified interim analysis of C omparison O f Efficacy and S afety Between TI cagrelor and C lopidogrel In Chinese (COSTIC), the ongoing prospective, observational, single-center trial. Primary outcomes include first occurrence of myocardial infarction, stroke, vascular death and Bleeding Academic Research Consortium (BARC) scale bleeding event. Propensity score matching (PSM) was carried out to adjust for differences in baseline characteristics between treatment arms. Results: In total, 4, 465 patients were enrolled. After PSM, the patients prescribed with ticagrelor had a lower incidence of primary efficacy endpoint relative to those with clopidogrel (0.6% vs. 1.4%, HR = 0.44, 95%CI: 0.22–0.89, p  = 0.019) at 1 month, but similar at 7 days, 6 months and 12 months. Further analysis indicated that the difference only exists in the subgroup of acute myocardial infarction (AMI) patients. With regard to safety, ticagrelor consistently increased the risk of BARC type 2 bleeding compared to clopidogrel at 1 month, 6 months and 12 months. Conclusions: These preliminary data indicate that ticagrelor is superior to clopidogrel with regard to major vascular thrombotic outcomes at 1 month, especially in the AMI population, but both groups are similar at 7 days, 6 months and 12 months. Ticagrelor consistently caused significantly more BARC type 2 bleeding. Graphical abstract: Image 1 Highlights: Ticagrelor is not superior to clopidogrel in the Chinese population. Ticagrelor decreased the risk of short-term thrombotic events in Chinese patients. Ticagrelor increased the risk of BARC type 2 bleeding compared to clopidogrel.